An Ontology of German Place Names - Sebastian Nagel (Corela)
My research has given rise to the construction of an ontology containing geographic entities and its German names. The ontology includes (1) the linguistic features of place names, such as their inflectional morphology and characteristic syntactic behaviour, (2) associates place names to geographic entities, and (3) the relationship between one geographic entity and another.